(untitled) (Conference on English Language Teaching, 2025)
This qualitative study explored the impact of technology-enhanced activities on critical thinking and self-regulated learning (SRL) in an online critical reading class for English Education students. Employing a phenomenological approach, data were collected through semi-structured interviews and the analysis of student artefacts from 30 participants. Thematic analysis revealed three primary themes: (1) Enhanced Critical Thinking Through Digital Engagement, highlighting how tools like digital annotation and online discussions deepened textual analysis and fostered critical discourse; (2) Self-Regulated Learning in the Online Space, demonstrating students’ use of goal setting, progress monitoring, and reflection; and (3) Perceived Challenges and Benefits of Technology Integration, which addressed both technical and logistical difficulties, as well as the flexibility and accessibility afforded by online learning. Findings indicate that strategically implemented technology-enhanced activities can significantly contribute to the development of critical thinking and SRL in online critical reading environments. The study provides practical implications for educators designing online language courses, emphasizing the importance of integrating technology to support higher-order thinking skills and self-directed learning